2013
DOI: 10.4293/108680813x13654754535791
|View full text |Cite
|
Sign up to set email alerts
|

Laparoscopic Colon Resections With Discharge Less Than 24 Hours

Abstract: Laparoscopic colon surgery that incorporates multimodal perioperative care may allow patients to be discharged within the first 24 hours.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
37
0
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(39 citation statements)
references
References 12 publications
0
37
0
2
Order By: Relevance
“…2 A number of studies have been conducted in order to shorten the hospital stay for patients who received a laparoscopic colectomy. 11 However, the operative time for a laparoscopic colectomy is much longer (approximately 200 minutes) than that of any other laparoscopic surgery such as an appendectomy or a cholecystectomy. Scheer reported that operative time could affect the postoperative complication rate.…”
Section: Discussionmentioning
confidence: 99%
“…2 A number of studies have been conducted in order to shorten the hospital stay for patients who received a laparoscopic colectomy. 11 However, the operative time for a laparoscopic colectomy is much longer (approximately 200 minutes) than that of any other laparoscopic surgery such as an appendectomy or a cholecystectomy. Scheer reported that operative time could affect the postoperative complication rate.…”
Section: Discussionmentioning
confidence: 99%
“…The combination of clinical features and CRP should allow for early discharge on day 3. Earlier discharge is possible and even same day discharge has been described following colorectal surgery [ 701 ]. Whatever day the patient is discharged on, there needs to be a clear contingency plan in the event of poor progress after discharge.…”
Section: Introductionmentioning
confidence: 99%
“…Our experience demonstrated a significant progressive reduction of LOS with increasing confidence with the ER protocol from 2013 to 2017. This trend allows us to preconize that within few years most of our patients could be possibly discharged within 24 h [ 18 ]. The implementation of the ER programme with reduced length of stay did not increase morbidity and readmission rate.…”
Section: Discussionmentioning
confidence: 99%